2019
DOI: 10.1021/acs.organomet.9b00373
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected CNN-to-CC Ligand Rearrangement in Pincer–Ruthenium Precatalysts Leads to a Base-Free Catalyst for Ester Hydrogenation

Abstract: We report the conversion of a series of CNN–pincer–ruthenium complexes Ru­(CNN)­HCl­(CO) to a CC-chelated form Ru­(CC)­(PR3)2H­(CO) on reaction with sodium tert-butoxide and monodentate phosphines. When the phosphine is triphenylphosphine, cis-phosphine complexes form at room temperature, which convert to the trans isomer at elevated temperatures. When the phosphine is tricyclohexylphosphine, only the trans-phosphine isomer is observed. The CC-chelated complexes are active catalysts for the hydrogenation of es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…In preliminary testing we found that the new complexes RuCNN-Et imine , RuCNN- i Pr imine , and RuPNN imine were active catalysts for ester hydrogenation without the need for added base. Since these imine-pincer complexes are formed by dehydroalkylation from amine-pincer complexes that are known catalysts for ester hydrogenation, , we hypothesized that the dehydroalkylation reaction might be a necessary step in catalyst activation. We began assessing this possibility by conducting comparative hydrogenation experiments side by side under the same conditions (toluene, 20 bar H 2 , 0.125 M hexyl hexanoate, 0.5% catalyst).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In preliminary testing we found that the new complexes RuCNN-Et imine , RuCNN- i Pr imine , and RuPNN imine were active catalysts for ester hydrogenation without the need for added base. Since these imine-pincer complexes are formed by dehydroalkylation from amine-pincer complexes that are known catalysts for ester hydrogenation, , we hypothesized that the dehydroalkylation reaction might be a necessary step in catalyst activation. We began assessing this possibility by conducting comparative hydrogenation experiments side by side under the same conditions (toluene, 20 bar H 2 , 0.125 M hexyl hexanoate, 0.5% catalyst).…”
Section: Results and Discussionmentioning
confidence: 99%
“…(2) Reactions catalyzed by the ruthenium­(II)–amine precursors showed release of ethane or propane, concomitant with the onset of catalysis. (3) An analogous NMe 2 -substituted variant of our RuCC precatalysts is nearly inactive for ester hydrogenation and also does not undergo dehydroalkylation to form a ruthenium(0)–imine complex.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 minutes, the aldehyde was completely consumed and hexyl hexanoate was the major product. ( Scheme 8). Further studies of this disproportionation reaction are in progress.…”
Section: Kineticsmentioning
confidence: 98%
“…For case of brevity, the focus will be on processes involving carbon dioxide and dinitrogen as the main substrates of interests, as well as chemical transformations promoting the valorization of biomass-derived molecules. Nevertheless, pincer complexes have achieved remarkable results in the (transfer) hydrogenation of a wide series of substrates such as ketones [385,[457][458][459][460][461][462], esters [40,179,220,386,400,[463][464][465][466][467][468][469][470][471][472][473][474][475][476][477], aldehydes [478][479][480], amides [67,[481][482][483][484][485], and imines [486,487]. After screening a range of amines, Prakash and Olah demonstrated the same concept using Ru-MACHO-BH and dimethylethylenediamine (5.3 wt% H2) which was successfully dehydrogenated in the presence of methanol resulting in a mixture of formamides [455].…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%